Pengaruh Komunikasi Terapeutik Bidan Ke Pasien Dan Pendampingan Suami Terhadap Kelancaran Proses Persalinan Normal Pada Ibu Melahirkan Di Puskesmas Babahbuloh Kabupaten Aceh Utara - Hartati Hartati; Risnawati Risnawati; Bima Suryantara (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Normal labor is a physiological process influenced by physical, psychological, and social support factors. Midwives’ therapeutic communication and husband support are forms of support that can help mothers feel calmer, more comfortable, and more confident during the labor process. Such support is expected to facilitate the smooth progress of normal labor. Objective to analyze the smoothness of the labor process in the presence of midwives’ therapeutic communication with patients and husband support. Study methods employed a quasi-experimental design with a post-test only control group design approach. The study was conducted at Babahbuloh Community Health Center, North Aceh Regency. The participants were women in labor who were divided into an experimental group and a control group. The sample was selected using purposive sampling, with a total of 34 respondents, consisting of 17 respondents in the experimental group and 17 respondents in the control group. The variables studied included midwives’ therapeutic communication, husband support, and the smoothness of the normal labor process. Data were analyzed using univariate analysis and bivariate analysis with the Mann–Whitney test. Results The Mann–Whitney test showed an Asymp. Sig. (2-tailed) value of 0.026 < 0.05. Therefore, the hypothesis was accepted, indicating that therapeutic communication between midwives and patients and husband support had a significant effect on the smoothness of the labor process. Conclusion therapeutic communication by midwives and husband support in the experimental group were better than those in the control group. The statistical analysis demonstrated that therapeutic communication between midwives and patients and husband support had a significant effect on the smoothness of the labor process. Therapeutic communication by midwives and husband support are important in providing psychological support, a sense of safety, and comfort to mothers throughout the labor process.